Pengaruh Brand Ambassador, Brand Trust, Brand Awereness, dan Brand Image Terhadap Keputusan Pembelian Produk Ultra Milk X Stray Kids - Juliana, Krisma; Priyono, Achmad Agus; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2026)
Abstract High competition in the milk beverage industry drives firms to adopt innovative marketing strategies, including the use of global brand ambassadors and brand equity enhancement. This study investigates the effects of brand ambassador, brand trust, brand awareness, and brand image on Generation Z’s purchasing decisions toward Ultra Milk X Stray Kids products. A quantitative survey was conducted with 90 respondents selected through snowball sampling, and the data were analyzed using multiple linear regression. The results show that all variables simultaneously influence purchasing decisions. However, only brand awareness has a positive and significant partial effect. These findings indicate that brand awareness is the key determinant of purchasing decisions among Generation Z consumers. Keywords: Brand Ambassador, Brand Trust, Brand Awareness, Brand Image, Purchasing Decision